The role of young scientists in the realm of physical culture and sports as a gauge of the environmental sustainability of university communities - Narkhov D.Yu. ,; Zhiltsova K.G. ,; Narkhova E.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to analysis of the factors that contribute to the reproduction of institutional and regulatory frameworks for scientific endeavors in the field of physical culture and sports, with a focus on their role in fostering the growth and preservation of youth-oriented scientific pursuits. Methods and structure of the study. A theoretical examination of the scholarly work of the higher education system has been conducted, with the addition of information on the involvement of young people in the process of defending their dissertations in the field of physical culture and sports, as well as insights from expert interviews in the Ural Federal District. The experts chosen for this study were academic and administrative personnel in the field of physical culture and sports, with a background in teaching and collaborative research with students. Results and conclusions. In the realm of governance, the process of unlocking the potential of youth science is founded on constructive forms of collaboration between university academic communities. The task of their systemic integration can be accomplished through the prism of value-driven interaction, rooted in the internalized social attitudes of the traditions of Russian education. In the long term, it is essential to reevaluate the institutional frameworks of management and administration, aiming to bridge or at least mitigate the divisions between communities. Within the university science of the physical culture and sports domain, it appears crucial to establish a "niche" for the sustainable growth of the scientific university ecosystem, fostering conditions for its qualitative reproduction through the harmonization of the interests of all stakeholders.